Pelaksanaan Asas Kebebasan Berkontrak Dalam Perjanjian Pembiayaan Konsumen (Studi Perjanjian Baku Dalam Perjanjian Pembiayaan Konsumen Antara Debitur dan PT. INDOMOBIL FINANCECabang Surakarta) - Kusuma, Maulana Trias Danu; , Septarina Budiwati, S.H., M.H; , Wardah Yuspin, S.H.,M.Kn.,Ph.D (2016)
The purpose of this study is to investigate the implementation of the principle of freedom of contract in the financing agreements as well as the problems that arise in the implementation of the principle of freedom of contract in consumer financing contracts and agreements which violate the principle of freedom of contract. Data analysis method is descriptive qualitative. Results of the research is in the implementation, the principle of freedom of contract in the financing agreements that not all the principles of freedom of contract are not fulfilled completely. The problems that arise in the implementation of the principle of freedom of contract is a standardized agreement form that made PT. Indomobil Finance Branch of Surakarta to save cost and time. Many of the provisions in the agreement that violates the principle of freedom of contract, although breaking the rules it has become something common, and avoid doing harm consumers PT. Indomobil Finance Branch of Surakarta